The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1590/s1516-635x2008000100006
|View full text |Cite
|
Sign up to set email alerts
|

Fatty acid profile of eggs of semi-heavy layers fed feeds containing linseed oil

Abstract: The incorporation of polyunsaturated fatty acids in chicken eggs by adding oils to the diets has been extensively studied. This experiment aimed at evaluating possible changes in the fatty acid profile of the eggs of layers fed diets supplemented with linseed and soybean oils. The experiment was performed using 192 29 week-old laying hens, distributed in a completely randomized design, into six treatments with four replicates of eight birds each. Treatments consisted of a control diet (no vegetable oil) and di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
18
3
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 30 publications
6
18
3
3
Order By: Relevance
“…The decreased OA contents in egg yolks might also be due to the inhibitory effects of PUFA against Δ9-desaturase enzyme activity, preventing the formation of OA from its precursors (Garg et al, 1988). The present trial confirmed the results of previous studies in which supplementation of n-3 PUFA in the hens' diet caused a reduction in OA content of yolks (Jiang et al, 1991;Bou et al, 2004;Souza et al, 2008;Ahmad et al, 2010).…”
Section: Egg-yolk Fatty Acidssupporting
confidence: 89%
“…The decreased OA contents in egg yolks might also be due to the inhibitory effects of PUFA against Δ9-desaturase enzyme activity, preventing the formation of OA from its precursors (Garg et al, 1988). The present trial confirmed the results of previous studies in which supplementation of n-3 PUFA in the hens' diet caused a reduction in OA content of yolks (Jiang et al, 1991;Bou et al, 2004;Souza et al, 2008;Ahmad et al, 2010).…”
Section: Egg-yolk Fatty Acidssupporting
confidence: 89%
“…In the current study SO effected in the highest n-6/n-3 ratio in comparison with the other oil sources. Souza et al (2008) reported that the supplementation of diets with LO increased (P<0.05) the unsaturated to saturated FA ratio in the egg yolk and they showed a linear effect of dietary linseed oil inclusion level on LNA:LA and n-6/n3 ratios (P<0.01). LNA can be desaturated and elongated in poultry liver to form DHA.…”
Section: Discussionmentioning
confidence: 96%
“…However, eggs are also very valuable source of proteins and contains many substances with biological function beyond basic nutrition (Mazalli et al, 2004;Laca et al, 2010;Liu et al, 2010). The eggs from hens provided standard feed are poor in linolenic acid (LNA; 18:3n-3), and does not contain eicosapentaenoic (EPA; 20:5n-3) and docosahexaenoic (DHA; 22:6n-3) fatty acids (Souza et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…See: http://creativecommons.org/licenses/by/2.5/za/Condition of use: The user may copy, distribute, transmit and adapt the work, but must recognise the authors and the South African Journal of Animal Science 6 to omega-3 (n-6 : n-3) fatty acids, as well as the presence of sufficient essential fatty acids (EFAs), could reduce the risk of CVD in humans (Surai et al, 2000;McNamara, 2000;Simopoulos, 2000). It is known that eggs are naturally low in α-linolenic acid and do not contain eicosapentoenoic (EPA) and docosahexaenoic (DHA) fatty acids (Souza et al, 2008). Fortunately, it is possible to overcome these deficiencies by means of dietary enrichment with essential fatty acids.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to their recognised value as a dense energy source, supplemental fats are excellent sources of essential fatty acids (EFAs), enhance the absorption of fat-soluble vitamins, increase the palatability of the diet and reduce dustiness of the feed (Celebi & Macit, 2008). Many studies (Scheideler & Froning, 1996;Cachaldora et al, 2006;Cachaldora et al, 2008;Souza et al, 2008) investigated dietary fatty acid saturation in the production of UFA enriched eggs, but few have focused on the long term effects that enriched diets might have on production performances of commercial layer hens over prolonged periods of time.…”
Section: Introductionmentioning
confidence: 99%